Tanggung Jawab Pelaku Usaha terhadap Konsumen Terkait Kartu Garansi yang Telah Lewat Masa Berlaku - Andreas Noval; Christine S.T Kansil (Syntax Literate, 2023)
The purpose of this research is to determine the responsibilities of business actors towards consumers regarding warranty cards that have expired according to Law Number 8 of 1999 concerning Consumer Protection. and to find out the legal consequences for consumers who have bad intentions towards business actors. This research uses normative legal research methods. The results of this research are that business actors no longer have responsibility for refrigerator products that are damaged because the guarantee period issued by the business actor and based on Minister of Trade Regulation 38/2019 has passed the time limit so that business actors are freed from responsibility as stated in Article 27 UUPK Juncto Article 19 Paragraph (5) UUPK. The legal consequences that occur for consumers who have bad intentions towards business actors can be in the form of absolute liability, giving rise to lawsuits for compensation from business actors. restrictions on consumer rights and loss of reputation for business actors.